A copper-containing wastewater recovery and treatment process

By performing multiple steps of modification of activated carbon, adsorption particles containing specific active groups were prepared, which solved the problem of poor adsorption effect of activated carbon when treating copper-containing wastewater, and significantly improved the adsorption and recovery effect of copper ions.

CN118745056BActive Publication Date: 2025-02-11广东中耀环境科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410822482.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-24
Publication Date
2025-02-11
Estimated Expiration
2044-06-24

AI Technical Summary

Technical Problem

In the prior art, when treating copper-containing wastewater, activated carbon has few holes and low surface modification degree, resulting in poor copper ion adsorption effect.

Method used

By performing multiple modification treatments on activated carbon with acidic solution, nitric acid solution, coupling agent, etc., adsorption particles containing hydroxyl groups, carboxyl groups, imine bonds and amino active groups were prepared for treatment of copper-containing wastewater.

Benefits of technology

The adsorption and recovery effect of copper ions is significantly improved, and the copper ions are fixed in the ring structure through coordination and chelation, forming a stable chelate.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to a copper-containing wastewater recovery and treatment process, and belongs to the technical field of wastewater metal recovery. A copper-containing wastewater recovery and treatment process comprises the steps of: adjusting the pH value of the copper-containing wastewater, filtering to remove solid impurities, placing in an adsorber containing adsorption particles, treating the solid-liquid mixture obtained after adsorption treatment by a solid-liquid cyclone separator to obtain a supernatant and an adsorbent; after the supernatant is tested and qualified, adjusting the pH value to neutral and then discharging, and the adsorbent is recovered and reused. The adsorption particles contain hydroxyl, carboxyl, imine bond and amino active groups, and when the adsorption particles are used to treat copper-containing wastewater, they have a significant copper ion adsorption and recovery effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal recovery from waste water and relates to a copper-containing waste water recovery and treatment process. Background Art

[0002] Copper metal wastewater is extremely harmful to water bodies and soil, so the treatment of copper-containing wastewater becomes increasingly important. Common treatment methods for heavy metal copper ions include chemical precipitation, adsorption, ion exchange, membrane separation, electrolysis, etc. Adsorption is the most commonly used method, usually using synthetic materials or natural mineral materials with large specific surface areas, easy to operate, and safety conditions can be well controlled.

[0003] As an adsorbent, activated carbon can effectively remove heavy metal ions from wastewater due to its developed pore structure, large specific surface area and super strong adsorption performance, and has gradually been widely used. However, unmodified activated carbon has fewer pores and fewer ions or ion groups with adsorption on the surface, so the adsorption effect is weak and the surface modifiability is low. Summary of the invention

[0004] The purpose of the present invention is to provide a copper-containing wastewater recovery and treatment process, which has a significant copper ion adsorption and recovery effect when the adsorption particles containing hydroxyl, carboxyl, imine bond and amino active groups in the adsorber are used to treat the copper-containing wastewater adsorption and recovery treatment.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A copper-containing wastewater recovery and treatment process comprises the following steps: adjusting the pH value of the copper-containing wastewater, filtering to remove solid impurities, placing the wastewater in an adsorber containing adsorption particles, treating the solid-liquid mixture obtained after the adsorption treatment in a solid-liquid cyclone separator to obtain a supernatant and an adsorbent; adjusting the pH value of the supernatant to neutral after testing to be qualified, and discharging the supernatant, and recovering the adsorbent for repeated use.

[0007] As a preferred technical solution of the present invention, the pH value is adjusted to 3-6; the adsorption treatment time is 4-5h; the number of the adsorbers is several, and the several adsorbers are connected in sequence; and the several adsorbers all contain the adsorption particles.

[0008] As a preferred technical solution of the present invention, the method for preparing the adsorption particles comprises the following steps:

[0009] S1, stirring and mixing the activated carbon and the acidic solution, washing the solid, drying in an oven, grinding, sieving, adding nitric acid solution, heating and stirring, washing the solid, and drying to obtain pretreated activated carbon;

[0010] S2, heating and mixing the pretreated activated carbon and anhydrous ethanol, slowly adding the coupling agent, heating and stirring, filtering and drying the solid, and obtaining modified activated carbon;

[0011] S3, placing the modified activated carbon in anhydrous ethanol, adding an auxiliary agent and ultrasonically mixing, then adding vinyl salicylaldehyde and stirring, adding an initiator under an inert atmosphere, heating and stirring, washing the solid, and drying to obtain aldehyde-modified activated carbon;

[0012] S4. Place the aldehyde-modified activated carbon in anhydrous ethanol, slowly add o-phenylenediamine, heat and stir, filter out the solvent, take the solid and wash it, and vacuum dry it to obtain the product.

[0013] As a preferred technical solution of the present invention, in step S1, the stirring and mixing time is 24-30h; the acidic solution is a 1mol / L hydrochloric acid aqueous solution; the mass fraction of the nitric acid solution is 10-12%; the screening is through a 200-mesh sieve; the heating and stirring is stirring at a speed of 300-400r / min and 60-65°C for 20-24h; and the washing is washing with deionized water until the washing solution is neutral.

[0014] As a preferred technical solution of the present invention, in step S1, the mass ratio of the activated carbon, the acid solution and the nitric acid solution is 1:2.0-2.5:3.0-3.2; the solvent of the nitric acid solution is deionized water; after being treated with the acid solution, the ash on the activated carbon can be removed, so that more pores are exposed and more adsorption sites are provided, and then the surface of the activated carbon after oxidation modification with the nitric acid solution contains a certain amount of oxygen-containing functional groups, such as carboxyl and hydroxyl groups, etc. These oxygen-containing functional groups also have a certain adsorption capacity for copper ions. At the same time, the activated carbon after oxidation modification can graft more coupling agents.

[0015] As a preferred technical solution of the present invention, in step S2, the heating and mixing is stirring at a temperature of 30-35°C and a stirring speed of 300-400r / min for 30-45min; the heating and stirring is stirring at 65-70°C for 5-6h; and the drying is drying to constant weight.

[0016] As a preferred technical solution of the present invention, in step S2, the mass ratio of the pretreated activated carbon, anhydrous ethanol and coupling agent is 10-12:35-40:6-8; the coupling agent is silane coupling agent G-570.

[0017] As a preferred technical solution of the present invention, in step S3, the ultrasonic mixing is 100-120W ultrasound for 5-8 minutes; the stirring mixing is stirring at a stirring speed of 200-300r / min for 30-45 minutes; the inert atmosphere is a nitrogen atmosphere; the heating stirring is stirring at a temperature of 70°C for 12-15 hours; and the washing is washing 3 times with anhydrous ethanol.

[0018] As a preferred technical solution of the present invention, in step S3, the mass ratio of the modified activated carbon, anhydrous ethanol, auxiliary agent and vinyl salicylaldehyde is 20-23:60-65:0.15-0.20:3-4:0.20-0.25; the auxiliary agent is succinic acid; the initiator is azobisisobutyronitrile; the present invention adopts succinic acid as an auxiliary agent, and succinic acid is self-attached to the surface and internal pores of the activated carbon through the carboxyl group, and utilizes the hydrogen bonding effect between the two carboxyl groups on the succinic acid and the vinyl salicylaldehyde to increase the contact between the vinyl salicylaldehyde and the pretreated activated carbon, thereby improving the grafting effect.

[0019] As a preferred technical solution of the present invention, in step S4, the heating and stirring is performed at 70-75°C for 7-8 hours; the washing is performed 3 times with anhydrous ethanol; and the vacuum drying is performed to a constant weight.

[0020] As a preferred technical solution of the present invention, in step S4, the mass ratio of the aldehyde-modified activated carbon, anhydrous ethanol and o-phenylenediamine is 12-13:40-45:3.5-4.0.

[0021] Beneficial effects of the present invention:

[0022] The surface of the adsorption particle material prepared by the present invention is mainly composed of imine bonds and amino groups, which coordinate with copper ions, supplemented by carboxyl and hydroxyl groups for chelating copper ions. The combined effect of the two fixes the copper ions in the ring structure to form a stable chelate, thereby significantly improving the adsorption and recovery effect of copper ions. DETAILED DESCRIPTION

[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0024] A copper-containing wastewater recovery and treatment process comprises the following steps: adjusting the pH value of the copper-containing wastewater, filtering to remove solid impurities, placing the wastewater in an adsorber containing adsorption particles, treating the solid-liquid mixture obtained after the adsorption treatment in a solid-liquid cyclone separator to obtain a supernatant and an adsorbent; adjusting the pH value of the supernatant to neutral after testing to find that it is qualified, and then discharging the supernatant, and recovering the adsorbent for repeated use.

[0025] The pH value is adjusted to 3-6; the adsorption treatment time is 4-5 hours; the number of the adsorbers is several, and the several adsorbers are connected in sequence; and the several adsorbers all contain the adsorption particles.

[0026] Example 1

[0027] The preparation method of the adsorption particles comprises the following steps:

[0028] S1, stirring and mixing the activated carbon and the acidic solution, washing the solid, drying in an oven, grinding, sieving, adding nitric acid solution, heating and stirring, washing the solid, and drying to obtain pretreated activated carbon;

[0029] In step S1, the stirring and mixing time is 24 hours; the acidic solution is a 1 mol / L hydrochloric acid aqueous solution; the mass fraction of the nitric acid solution is 10%; the sieving is through a 200 mesh sieve; the heating and stirring is stirring at a speed of 300 r / min and 60° C. for 20 hours; the washing is washing with deionized water until the washing solution is neutral;

[0030] The mass ratio of the activated carbon, the acid solution and the nitric acid solution is 1:2.0:3.0;

[0031] S2, heating and mixing the pretreated activated carbon and anhydrous ethanol, slowly adding the coupling agent, heating and stirring, filtering and drying the solid, and obtaining modified activated carbon;

[0032] In step S2, the heating and mixing is stirring at 30°C and 300 r / min for 30 min; the heating and stirring is stirring at 65°C for 5 h; and the drying is drying to constant weight;

[0033] In step S2, the mass ratio of the pretreated activated carbon, anhydrous ethanol and coupling agent is 10:35:6; the coupling agent is silane coupling agent G-570;

[0034] S3, placing the modified activated carbon in anhydrous ethanol, adding an auxiliary agent and ultrasonically mixing, then adding vinyl salicylaldehyde and stirring, adding an initiator under an inert atmosphere, heating and stirring, washing the solid, and drying to obtain aldehyde-modified activated carbon;

[0035] In step S3, the ultrasonic mixing is 100W ultrasound for 5 minutes; the stirring mixing is stirring at a stirring speed of 200 r / min for 30 minutes; the inert atmosphere is a nitrogen atmosphere; the heating stirring is stirring at a temperature of 70° C. for 12 hours; and the washing is washing with anhydrous ethanol for 3 times;

[0036] In step S3, the mass ratio of the modified activated carbon, anhydrous ethanol, auxiliary agent and vinyl salicylaldehyde is 20:60:0.15:3:0.20; the auxiliary agent is succinic acid; the initiator is azobisisobutyronitrile;

[0037] S4, placing the aldehyde-modified activated carbon in anhydrous ethanol, slowly adding o-phenylenediamine, heating and stirring, filtering off the solvent, washing the solid, and vacuum drying to obtain;

[0038] In step S4, the heating and stirring is performed at 70° C. and stirring for 7 hours; the washing is performed 3 times with anhydrous ethanol; and the vacuum drying is performed to a constant weight;

[0039] In step S4, the mass ratio of the aldehyde-modified activated carbon, anhydrous ethanol and o-phenylenediamine is 12:40:3.5.

[0040] Example 2

[0041] The preparation method of the adsorption particles comprises the following steps:

[0042] S1, stirring and mixing the activated carbon and the acidic solution, washing the solid, drying in an oven, grinding, sieving, adding nitric acid solution, heating and stirring, washing the solid, and drying to obtain pretreated activated carbon;

[0043] In step S1, the stirring and mixing time is 27 hours; the acidic solution is a 1 mol / L hydrochloric acid aqueous solution; the mass fraction of the nitric acid solution is 11%; the sieving is through a 200 mesh sieve; the heating and stirring is stirring at a speed of 350 r / min and 62° C. for 22 hours; the washing is washing with deionized water until the washing solution is neutral;

[0044] The mass ratio of the activated carbon, the acid solution and the nitric acid solution is 1:2.2:3.1;

[0045] S2, heating and mixing the pretreated activated carbon and anhydrous ethanol, slowly adding the coupling agent, heating and stirring, filtering and drying the solid, and obtaining modified activated carbon;

[0046] In step S2, the heating and mixing is stirring at 32°C and 350 r / min for 38 min; the heating and stirring is stirring at 68°C for 5.5 h; and the drying is drying to constant weight;

[0047] In step S2, the mass ratio of the pretreated activated carbon, anhydrous ethanol and coupling agent is 11:38:7; the coupling agent is silane coupling agent G-570;

[0048] S3, placing the modified activated carbon in anhydrous ethanol, adding an auxiliary agent and ultrasonically mixing, then adding vinyl salicylaldehyde and stirring, adding an initiator under an inert atmosphere, heating and stirring, washing the solid, and drying to obtain aldehyde-modified activated carbon;

[0049] In step S3, the ultrasonic mixing is 110W ultrasound for 6 minutes; the stirring mixing is stirring at a stirring speed of 250r / min for 38 minutes; the inert atmosphere is a nitrogen atmosphere; the heating stirring is stirring at a temperature of 70°C for 14 hours; the washing is washing with anhydrous ethanol for 3 times;

[0050] In step S3, the mass ratio of the modified activated carbon, anhydrous ethanol, auxiliary agent and vinyl salicylaldehyde is 22:62:0.18:3.5:0.22; the auxiliary agent is succinic acid; the initiator is azobisisobutyronitrile;

[0051] S4, placing the aldehyde-modified activated carbon in anhydrous ethanol, slowly adding o-phenylenediamine, heating and stirring, filtering off the solvent, washing the solid, and vacuum drying to obtain;

[0052] In step S4, the heating and stirring is performed at 72° C. and stirring for 7.5 hours; the washing is performed 3 times with anhydrous ethanol; and the vacuum drying is performed to a constant weight;

[0053] In step S4, the mass ratio of the aldehyde-modified activated carbon, anhydrous ethanol and o-phenylenediamine is 12.5:42:3.8.

[0054] Example 3

[0055] The preparation method of the adsorption particles comprises the following steps:

[0056] S1, stirring and mixing the activated carbon and the acidic solution, washing the solid, drying in an oven, grinding, sieving, adding nitric acid solution, heating and stirring, washing the solid, and drying to obtain pretreated activated carbon;

[0057] In step S1, the stirring and mixing time is 30 hours; the acidic solution is a 1 mol / L hydrochloric acid aqueous solution; the mass fraction of the nitric acid solution is 12%; the sieving is through a 200 mesh sieve; the heating and stirring is stirring at a speed of 400 r / min and 65° C. for 24 hours; the washing is washing with deionized water until the washing solution is neutral;

[0058] The mass ratio of the activated carbon, the acid solution and the nitric acid solution is 1:2.5:3.2;

[0059] S2, heating and mixing the pretreated activated carbon and anhydrous ethanol, slowly adding the coupling agent, heating and stirring, filtering and drying the solid, and obtaining modified activated carbon;

[0060] In step S2, the heating and mixing is stirring at 35°C and 400 r / min for 45 min; the heating and stirring is stirring at 70°C for 6 h; and the drying is drying to constant weight;

[0061] In step S2, the mass ratio of the pretreated activated carbon, anhydrous ethanol and coupling agent is 12:40:8; the coupling agent is silane coupling agent G-570;

[0062] S3, placing the modified activated carbon in anhydrous ethanol, adding an auxiliary agent and ultrasonically mixing, then adding vinyl salicylaldehyde and stirring, adding an initiator under an inert atmosphere, heating and stirring, washing the solid, and drying to obtain aldehyde-modified activated carbon;

[0063] In step S3, the ultrasonic mixing is 120W ultrasound for 8 minutes; the stirring mixing is stirring at a stirring speed of 300r / min for 45 minutes; the inert atmosphere is a nitrogen atmosphere; the heating stirring is stirring at a temperature of 70°C for 15 hours; the washing is washing with anhydrous ethanol for 3 times;

[0064] In step S3, the mass ratio of the modified activated carbon, anhydrous ethanol, auxiliary agent and vinyl salicylaldehyde is 23:65:0.20:4:0.25; the auxiliary agent is succinic acid; the initiator is azobisisobutyronitrile;

[0065] S4, placing the aldehyde-modified activated carbon in anhydrous ethanol, slowly adding o-phenylenediamine, heating and stirring, filtering off the solvent, washing the solid, and vacuum drying to obtain;

[0066] In step S4, the heating and stirring is performed at 75° C. and stirring for 8 hours; the washing is performed 3 times with anhydrous ethanol; and the vacuum drying is performed to a constant weight;

[0067] In step S4, the mass ratio of the aldehyde-modified activated carbon, anhydrous ethanol and o-phenylenediamine is 13:45:4.0.

[0068] Comparative Example 1

[0069] Compared with Example 3, the difference in Comparative Example 1 is that activated carbon is used instead of pretreated activated carbon, and the other components, preparation steps and parameters are the same.

[0070] Comparative Example 2

[0071] Compared with Example 3, the difference in Comparative Example 2 is that no coupling agent is used in step S2, and the other components, preparation steps and parameters are the same.

[0072] Comparative Example 3

[0073] Compared with Example 3, the difference of Comparative Example 3 is that no auxiliary agent is used in step S3, and the other components, preparation steps and parameters are the same.

[0074] Comparative Example 4

[0075] Compared with Example 3, Comparative Example 4 is different in that step S3 uses salicylaldehyde instead of vinyl salicylaldehyde, and the remaining components, preparation steps and parameters are the same.

[0076] Comparative Example 5

[0077] Compared with Example 3, the difference in Comparative Example 5 is that step S4 is not performed, and the remaining components, preparation steps and parameters are the same.

[0078] Comparative Example 6

[0079] Compared with Example 3, the difference in Comparative Example 6 is step S3, and step S4 is not performed in Comparative Example 6;

[0080] Step S3: placing the modified activated carbon in anhydrous ethanol, adding an auxiliary agent and ultrasonically mixing, then adding o-phenylenediamine and stirring and mixing, rotary evaporating to remove the solvent, and drying to obtain the result;

[0081] The remaining components, preparation steps and parameters were the same.

[0082] The following tests were performed on Examples 1-3 and Comparative Examples 1-6, respectively, and the test results are shown in Table 1.

[0083] Under the conditions of an initial mass concentration of 50 mg / L of divalent copper in simulated wastewater, pH=6, a volume of 50 mL, an adsorption particle (Example 1-3, Comparative Example 1-6) of 10 mg, a temperature of 25°C, and a stirring rate of 150 r / min, adsorption was carried out for 5 hours, and the removal rate of divalent copper was calculated. The higher the removal rate, the better the adsorption effect.

[0084] Wherein, Cu removal rate (%) = (P0-P1) / P0×100%; P0 is the initial copper ion mass concentration of the wastewater, mg / L; P1 is the copper ion mass concentration of the wastewater after adsorption is completed.

[0085] Table 1

[0086] Cu removal rate (%) Example 1 99.3 Example 2 99.1 Example 3 99.4 Comparative Example 1 88.6 Comparative Example 2 81.3 Comparative Example 3 89.1 Comparative Example 4 79.4 Comparative Example 5 73.2 Comparative Example 6 72.5

[0087] From the test results in Table 1, it can be seen that compared with Comparative Examples 1-6, the adsorption effect of the adsorption particles prepared in Examples 1-3 of the present invention on copper ions is significantly better than that in Comparative Examples 1-6. The surface of the adsorption particle material prepared in the present invention is mainly composed of imine bonds and amino groups, which coordinate with copper ions, supplemented by the chelation of copper ions by carboxyl and hydroxyl groups. The combined effect of the two fixes the copper ions in the ring structure to form a stable chelate, thereby significantly improving the adsorption effect on copper ions. This is because, after the activated carbon of the scheme of the present invention is treated with an acidic solution, the ash on the activated carbon can be removed, so that more pores are exposed and more adsorption sites are provided. Then, the surface of the activated carbon after oxidation modification with a nitric acid solution contains a certain amount of oxygen-containing functional groups, such as carboxyl and hydroxyl groups, which also have a certain adsorption capacity for copper ions. At the same time, the activated carbon after oxidation modification contains a large amount of hydroxyl and carboxyl groups, so that it can be grafted with more coupling agents and introduce active carbon-carbon double bonds. Then, succinic acid is used as an auxiliary agent to form an electrostatic effect on vinyl salicylaldehyde through the interaction of hydrogen bonds, thereby increasing the adsorption capacity of vinyl. The contact between salicylaldehyde and pretreated activated carbon improves the modification effect of the aldehyde group, so that the modified activated carbon forms a chemical bond with vinyl salicylaldehyde, which increases the stability and introduces more aldehyde groups. Finally, an imine bond is formed between o-phenylenediamine containing an amino group and the aldehyde group of vinyl salicylaldehyde, which increases its stability and introduces an imine bond with a stronger adsorption effect. Finally, a structure is formed which is mainly composed of imine bonds and amino groups, supplemented by the coordination and chelation of copper ions with carboxyl and hydroxyl groups. The combined action of the two fixes the copper ions in the ring structure to form a stable chelate, thereby significantly improving the adsorption effect on copper ions.

[0088] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A copper-containing wastewater recovery and treatment process, characterized in that: The recovery and treatment process comprises the following steps: adjusting the pH value of the copper-containing wastewater, filtering to remove solid impurities, placing the wastewater in an adsorber containing adsorption particles, treating the solid-liquid mixture obtained after the adsorption treatment in a solid-liquid cyclone separator to obtain a supernatant and an adsorbent; adjusting the pH value of the supernatant to neutral after testing to be qualified, and discharging the supernatant, and recovering and reusing the adsorbent; The preparation method of the adsorption particles comprises the following steps: S1, stirring and mixing the activated carbon and the acidic solution, washing the solid, drying in an oven, grinding, sieving, adding nitric acid solution, heating and stirring, washing the solid, and drying to obtain pretreated activated carbon; S2, heating and mixing the pretreated activated carbon and anhydrous ethanol, slowly adding a coupling agent, heating and stirring, filtering and drying the solid, and obtaining modified activated carbon; the mass ratio of the pretreated activated carbon, anhydrous ethanol and coupling agent is 10-12:35-40:6-8; the coupling agent is silane coupling agent G-570; S3, placing the modified activated carbon in anhydrous ethanol, adding an auxiliary agent and ultrasonically mixing, then adding vinyl salicylaldehyde and stirring, adding an initiator under an inert atmosphere, heating and stirring, washing the solid, and drying to obtain aldehyde-modified activated carbon; the mass ratio of the modified activated carbon, anhydrous ethanol, auxiliary agent and vinyl salicylaldehyde is 20-23:60-65:0.15-0.20:3-4:0.20-0.25; the auxiliary agent is succinic acid; the initiator is azobisisobutyronitrile; S4. Place the aldehyde-modified activated carbon in anhydrous ethanol, slowly add o-phenylenediamine, heat and stir, filter out the solvent, take out the solid, wash it, and vacuum dry it to obtain the product; the mass ratio of the aldehyde-modified activated carbon, anhydrous ethanol and o-phenylenediamine is 12-13:40-45:3.5-4.

0.

2. A copper-containing wastewater recovery and treatment process according to claim 1, characterized in that: The pH value is adjusted to 3-6; the adsorption treatment time is 4-5 hours; the number of the adsorbers is several, and the several adsorbers are connected in sequence; and the several adsorbers all contain the adsorption particles.

3. A copper-containing wastewater recovery and treatment process according to claim 1, characterized in that: In step S2, the heating and mixing is stirring at a temperature of 30-35°C and a stirring speed of 300-400 r / min for 30-45 min; the heating and stirring is stirring at 65-70°C for 5-6 h; and the drying is drying to constant weight.

4. A copper-containing wastewater recovery and treatment process according to claim 1, characterized in that: In step S3, the ultrasonic mixing is 100-120W ultrasound for 5-8 minutes; the stirring mixing is stirring at a stirring speed of 200-300r / min for 30-45 minutes; the inert atmosphere is a nitrogen atmosphere; the heating stirring is stirring at a temperature of 70°C for 12-15h; and the washing is washing 3 times with anhydrous ethanol.

5. A copper-containing wastewater recovery and treatment process according to claim 1, characterized in that: In step S1, the stirring and mixing time is 24-30 hours; the acidic solution is a 1 mol / L hydrochloric acid aqueous solution; the mass fraction of the nitric acid solution is 10-12%; the screening is through a 200 mesh sieve; the heating and stirring is stirring at a speed of 300-400 r / min and 60-65° C. for 20-24 hours.

6. A copper-containing wastewater recovery and treatment process according to claim 1, characterized in that: In step S4, the heating and stirring is performed at 70-75° C. and stirring for 7-8 hours; the washing is performed 3 times with anhydrous ethanol; and the vacuum drying is performed to a constant weight.

Citation Information

Patent Citations

  • Treatment process of cupriferous waste water

    CN105984977A

  • TVOC-resistant powder, indoor TVOC degradation floral type coating and preparation method thereof

    CN113117649A